Real-world utilization of darbepoetin alfa in cancer chemotherapy patients. (January 2019) - Pan, Xiaoyun (Lucy); Nordstrom, Beth L; MacLachlan, Sharon; Lin, Junji; Xu, Hairong; Sharma, Anjali; Chandler, David; Li, Xiaoyan (Shawn)
Objectives: To provide an understanding of darbepoetin alfa dose patterns in cancer patients undergoing myelosuppressive chemotherapy starting from 2011. Study design: This is a retrospective cohort study using a proprietary outpatient oncology database. Methods: Metastatic, solid tumor cancer patients receiving concomitant myelosuppressive chemotherapy and darbepoetin alfa with an associated hemoglobin <10 g/dL during 2011–2015 were identified. The analysis was restricted to the first continuous exposure to chemotherapy agents (maximum allowable gap of 90 days between consecutive exposures) with darbepoetin alfa for each eligible patient. Initial, maintenance, weekly, and cumulative doses of darbepoetin alfa were examined across all darbepoetin alfa users. Subgroup analyses were conducted by chemotherapy type, baseline hemoglobin level, year of chemotherapy, solid tumor type, and initial dosing schedule. Differences in weekly doses across subgroups were evaluated using Wilcoxon rank-sum tests. Results: Among 835 eligible patients, over 90% were 50 years or older. Mean chemotherapy course duration was 248 days, and mean duration of darbepoetin alfa treatment was 106 days. The mean weekly darbepoetin alfa dose was 110 µg. Patients received a mean of 4.3 darbepoetin alfa injections in the first chemotherapy course. There were no statistically significant differences (all P values > .05) in weekly dose by chemotherapy type, baseline hemoglobin level, year of chemotherapy, or solid tumor type. Conclusion: The average weekly darbepoetin alfa dose among metastatic cancer patients with chemotherapy-induced anemia from this study was 110 µg, which was lower than the labeled dosage for most adults. This estimate did not differ over time, across chemotherapy regimens, baseline hemoglobin levels, or solid tumor types.